DEIXIS ANALYSIS IN THE SHORT STORY “THE LITTLE OLD WOMAN WHO LIVED IN A SHOE” BY JOSEPH MARTIN KRONHEIM - Delia Lestyanada (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The research is about deixis used in the short story “The Little Old Woman Who Lived in a Shoe” by Joseph Martin Kronheim. The aim of this research is to know the categories and the meaning of deixis used in the short story. The theory used in this reseacrh is Levinson’s theory which stated that deixis can be classified into five parts, namely personal deixis, place deixis, time deixis, social deixis, and deixis discourse. The article specifically describes personal deixis, time deixis, and place deixis in the short story. The researcher used qualitative descriptive method. The data was collected by using gathering observation approach followed by nonparticipant observational technique and combined with noting technique. Based on the result of the analysis, the researcher concluded that there are personal deixis, place deixis, and time deixis words used in the short story “The Little Old Woman Who Lived in a Shoe” by Joseph Martin Kronheim. The number of the deictic words is dominated by personal deixis. Keywords:Deixis, short story, The Little Old Woman Who Lived in a Shoe by Joseph Martin Kronheim